PROBLEMS OF INTERPRETING AND STUDYING CLASSICAL TEXTS - Ozoda Tojiboyeva; Mina Karwoni (Journals Park Publishing, 2024)
Understanding the content of classical literature presents challenges for today's readers. This is because the multilayered nature of classical texts and the religious and Sufi concepts embedded within them require explanations. Today, interpretations, comments, prose narratives, and analyses play a significant role in understanding the works of Alisher Navoi. This article provides information about additional interpretations created within the framework of understanding Navoi's works.
Keywords: interpretation, commentary, prose narrative, epic, poetry, prose, explanation, dictionary.